2022
DOI: 10.3390/biomedicines10081987
|View full text |Cite
|
Sign up to set email alerts
|

CK2 and the Hallmarks of Cancer

Abstract: Cancer is a leading cause of death worldwide. Casein kinase 2 (CK2) is commonly dysregulated in cancer, impacting diverse molecular pathways. CK2 is a highly conserved serine/threonine kinase, constitutively active and ubiquitously expressed in eukaryotes. With over 500 known substrates and being estimated to be responsible for up to 10% of the human phosphoproteome, it is of significant importance. A broad spectrum of diverse types of cancer cells has been already shown to rely on disturbed CK2 levels for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 572 publications
1
8
0
Order By: Relevance
“…Treatment with AB668 strongly impacted cancer cell viability resulting in apoptotic cell death, while sparing healthy cells. A long-held view has suggested that malignant cells are dependent upon sustained CK2 signaling for survival thereby exhibiting an exquisite sensitivity to CK2 inhibition (Ruzzene et al, 2010; Roffey et al, 2021; Firnau et al, 2022). Conversely, non-cancer cells are more resistant to induction of cell death on downregulation of CK2 activity, which is the expected basis for safely using a pharmacological chemical inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with AB668 strongly impacted cancer cell viability resulting in apoptotic cell death, while sparing healthy cells. A long-held view has suggested that malignant cells are dependent upon sustained CK2 signaling for survival thereby exhibiting an exquisite sensitivity to CK2 inhibition (Ruzzene et al, 2010; Roffey et al, 2021; Firnau et al, 2022). Conversely, non-cancer cells are more resistant to induction of cell death on downregulation of CK2 activity, which is the expected basis for safely using a pharmacological chemical inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The higher sensitivity of cancer cells to CK2 inhibition, as compared to their healthy counterparts, led to the hypothesis of a “non-oncogenic” CK2 addiction of cancer cells (Luo et al, 2009; Ruzzene et al, 2010). Compiling evidence from the literature suggests that CK2 modulates all hallmarks of cancer (Firnau et al, 2022). Consequently, CK2 is considered as a “master regulator” and a promising therapeutic target to treat different human tumors (Roffey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phosphorylation of FADD at Ser200 indicated its nuclear localization, which is influenced by Casein kinase 2 (CK2). Elevated level of CK2 have been detected in malignant cells and various types of cancers, such as lung, colon, breast, ovarian, pancreatic, and prostate cancer [ 13 , 63 ]. Interestingly, phosphorylation of FADD at serine 194 mediates the nuclear localization of FADD for genomic surveillance [ 54 ].…”
Section: Structure and Cellular Localization Of Fas-associated Death ...mentioning
confidence: 99%
“…Among these kinases, Casein kinase 2 (CK2) is a conserved serine/threonine kinase in many species and has recently gained attention due to its involvement in many cellular processes, such as cell growth, death, and migration. CK2 is known to regulate diverse signaling pathways by phosphorylating a wide range of protein substrates involved in cell adhesion, cytoskeletal organization, and EMT [ 30 , 31 ]. CK2-mediated phosphorylation of key substrates has been implicated as a critical step in metastasis by modulating activities of transcription factors, cell adhesion molecules, and components of signaling pathways.…”
Section: Introductionmentioning
confidence: 99%